2017
DOI: 10.1145/3134733
|View full text |Cite
|
Sign up to set email alerts
|

Crowdcasting

Abstract: We designed and developed a "crowdcasting" prototype to enable remote people to participate in a live event through a collection of live streams coming from the event. Viewers could select from a choice of streams and interact with the streamer and other viewers through text comments and heart reactions. We deployed the prototype in three live events: a Winterfest holiday festival, a local Women's March, and the South by Southwest festival. We found that viewers actively switched among a choice of streams from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…To compare these two storyline developments, our research team refined the scratch to a higher fidelity design and then conducted a survey study with N=50 volunteer participants (i.e., 21 males, 1 non-binary, 2 prefer not to disclose, ages 18-34, Mean=21) recruited via email, word of mouth, and snowball sampling, who have more than one year of live stream watching experience. According to previous study, paid participants tend to act differently than volunteer participants of live streams [135]. Thus, we centered on recruiting volunteer participants who were intrinsically motivated to watch live streams [94,95].…”
Section: Crafting the Narrative: Iterative Designmentioning
confidence: 99%
See 1 more Smart Citation
“…To compare these two storyline developments, our research team refined the scratch to a higher fidelity design and then conducted a survey study with N=50 volunteer participants (i.e., 21 males, 1 non-binary, 2 prefer not to disclose, ages 18-34, Mean=21) recruited via email, word of mouth, and snowball sampling, who have more than one year of live stream watching experience. According to previous study, paid participants tend to act differently than volunteer participants of live streams [135]. Thus, we centered on recruiting volunteer participants who were intrinsically motivated to watch live streams [94,95].…”
Section: Crafting the Narrative: Iterative Designmentioning
confidence: 99%
“…We chose to conduct a small-scale deployment study using a 'staging instance' [63] due to methodological limitations of conducting this study at scale. Previous research has found that larger population samples are needed to thoroughly evaluate the usability of a live streaming tool [94,102], however, a large proportion of Amazon Mechanical Turk-hired viewers tend to be more active than volunteer viewers [135], which might lead to distorted results. Moreover, as discovered in a pilot study, participants would not actively send negative comments throughout the experiment.…”
Section: Deployment Study and Post-hoc Reviewsmentioning
confidence: 99%
“…live events [56], and outdoor activities [36], has been shown to foster participatory entertainment experiences in the livestreaming community [19,32]. Livestreaming also enables knowledge sharing.…”
Section: Livestreaming and Its Practice In Chinamentioning
confidence: 99%
“…Além disso, essas reac ¸ões podem representar as emoc ¸ões que o espectador está sentindo no momento. Outras formas de interac ¸ão também são notadas, como, comentários de texto [Tang et al 2017], stickers [Chen et al 2019], votac ¸ões [Hamilton et al 2014], doac ¸ões e presentes ao streamer [Lu et al 2018].…”
Section: Live Streaming E Engajamentounclassified
“…Plataformas de streaming oferecem recursos interativos que auxiliam a identificar o engajamento e promover interatividade em lives, como likes [Tang et al 2017], comentários [Hamilton et al 2014], compartilhamentos [Raman et al 2018] e votac ¸ões [Lessel et al 2017]. Entretanto, não há uma forma que sintetize tais recursos interativos a fim de compreender se espectadores estão engajados com o conteúdo.…”
Section: Introduc ¸ãOunclassified